Polymorphism and cocrystal salt formation of 2-((2, 6-dichlorophenyl)amino)benzoic acid, harvest of a second form of 2-((2, 6-dimethylphenyl)amino)benzoic acid, and isomorphism between the two systems. Issue 3 (23rd December 2021) - Zhoujin, Yunping; Li, Yuping; Zhang, Mingtao; Parkin, Sean; Guo, Ju; Li, Tonglei; Yu, Faquan; Long, Sihui
Abstract : Isomorphism and isostructurality were observed between form I of 2-((2, 6-dimethylphenyl)amino)benzoic acid and its analog 2-((2, 6-dichlorophenyl)amino)benzoic acid, which suggests double Cl–CH3 exchange also leads to structural similarity. Abstract : 2-((2, 6-Dichlorophenyl)amino)benzoic acid (2-DCABA), a potential non-steroidal anti-inflammatory drug and an analog of 2-((2, 6-dimethylphenyl)amino)benzoic acid (HDMPA) was synthesized and its polymorphism was studied to investigate the effect of double Cl–CH3 exchange. Three forms-two polymorphs (I and II ) and one cocrystal salt (S )-were obtained through polymorph screening in a variety of solvents, and the elusive single crystals of form II of HDMPA were harvested through melt crystallization. The crystal forms were characterized by single-crystal X-ray diffraction, powder X-ray diffraction (PXRD), DSC, and FT-IR. Isomorphism and isostructurality were observed between the form I of each system. The polymorphism of 2-DCABA seems to stem from the conformational flexibility of the molecule, similar to that of HDMPA. Hirshfeld analysis revealed different intermolecular interactions contributing to the stability of the crystal form I of 2-DCABA and HDMPA-I, despite their structural similarity.